Adjournment of Civil Lawsuits (AComparative Study) - Abdulali Mutlak, Assist. Lect. Thikra (Basra studies journal, 2024)
The general rule governing the course of civil lawsuits is to continue their proceedings without cessation or hindrance. However, this rule is subject to various exceptions for multiple justifications. Postponement of a civil lawsuit is one of these exceptions, which counters this general rule as it delays the lawsuit for a period of time. The legislator has regulated the mechanism for the conduct of civil lawsuits and granted the competent judicial authority the power to postpone civil lawsuits whenever necessary. This should be for a suitable period not exceeding the maximum limit set by law, whether done voluntarily or upon request of one of the litigants. Postponing a civil lawsuit entails several effects related to prolonging the litigation process and delaying the resolution of the civil lawsuit. If the postponement of a civil lawsuit is a legal means to grant litigants sufficient time to defend their rights, it necessitates granting litigants time to exercise their procedural rights and duties. Preserving time requires that postponement not be used as a tool for procrastination and delay in prolonging the litigation process, leading to a waste of time, effort, and increased financial costs. Therefore, the right to postponement must be within the permissible scope.